El puente entre el observar y el explicar.: Subjetividad y objetividad en el pensar científico y su relevancia en las psicoterapias. (VITAE Academia Biomédica Digital, 2002)
The author discusses the similarities and common difficulties faced by the natural sciences and the psychotherapies in their construction of explanatory theories. Some examples show how subjective factors are always present and determine the way we can observe apparent hard objective data. The interplay between theory and observation can lead to a false or distorted register of the data in the service of the defense of creeds, beliefs, faith or the adherence to a supposedly valid theoretical formulation. The frequent disregard and the reluctance to apply rigorous scientific methodology when dealing with observable psychological data have also resulted in faulty theoretical constructs that resist any scientific proof. Nevertheless, many psychological theories have persisted and have been sentenced as valid despite their illogical or refutable proposals.